Sustainable development, green economy - ways of implementation in Russia: regional aspecto - Kudinova, Galina Eduardovna; Korostelev, Aleksandr A.; Rozenberg, Anastasia G.; Tkachev, Boris Pavlovich; VorokovaNodira Кhasanovna (Cuestiones Políticas, 2020)
Increasing threats of biodiversity loss, recent emerging environmental crises and disasters, environmental degradation caused by increased industrial production, increased anthropogenic pressures, and population growth since the mid-20th century have created a threat for the lives of current and future generations. The concern of the world community with environmental problems was expressed in the main forums, summits and was marked by the development of strategies aimed at sustainable development and the change in the economic path towards the formation of environmental protection technologies and the creation of an economy. green globally and regionally. Many prominent scientists considered the tasks of protecting the environment and sustainable regional development, but the problems of the green economy and the transition to sustainable development in the region are not fully understood. In this sense, the objective of the research is to consider the possibility of implementing a strategy for sustainable development and a "green economy" in Russia (regional aspect).